2019
DOI: 10.1126/sciadv.aax8648
|View full text |Cite
|
Sign up to set email alerts
|

Extreme Zr stable isotope fractionation during magmatic fractional crystallization

Abstract: Zr stable isotopes exhibit >5‰ fractionations at magmatic conditions, yielding novel insights into melt chemical evolution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
95
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(104 citation statements)
references
References 55 publications
3
95
6
Order By: Relevance
“…The δ 94 Zr values of all analyzed zircons range from −0.86‰ to 0.41‰, with an average of −0.04 ± 0.39‰ (2SD, n = 237). The overall range (1.27‰) is larger than recently reported bulk rocks (0.582‰) (21), but smaller than that (∼5‰) observed in zircon and baddeleyite crystals from anorthosite FC1 (15,22).…”
Section: Mafic-intermediate Plutonic Rocks and Zircons From The Gangdcontrasting
confidence: 61%
See 4 more Smart Citations
“…The δ 94 Zr values of all analyzed zircons range from −0.86‰ to 0.41‰, with an average of −0.04 ± 0.39‰ (2SD, n = 237). The overall range (1.27‰) is larger than recently reported bulk rocks (0.582‰) (21), but smaller than that (∼5‰) observed in zircon and baddeleyite crystals from anorthosite FC1 (15,22).…”
Section: Mafic-intermediate Plutonic Rocks and Zircons From The Gangdcontrasting
confidence: 61%
“…and an α of 1.00106 was suggested accordingly (22). While these studies reached opposite conclusions, they both suggested that zircon crystallization would fractionate the Zr isotope composition of the melt.…”
Section: Significancementioning
confidence: 98%
See 3 more Smart Citations